G102(P) The role of stiripentol in intractable epilepsy. (27th April 2016) - Mount, C; Sharif, N; Hindley, D
Abstract : Aims: Intractable epilepsy is a significant condition, heavily reliant on chronic administration of anti-epileptic drugs (AEDs). It causes considerable morbidity, with undesired side-effects. Currently, stiripentol (STP) has orphan status for Dravet Syndrome (DS), when used in combination with sodium valproate (VPA) and clobazam (CLB). We report five children (only one with DS), who responded well to this triple therapy regime. Methods: We present five observational cases of intractable epilepsy, treated with STP as an adjunct therapy, with remarkable results. Results: Case One Four year old girl with myoclonic jerks and absences from two years, causing persistent daily seizures. Co-morbidities include global development delay of unknown cause. Previously tried on four AEDs, including VPA and CLB. Rapid improvement when triple therapy initiated. Case Two Seven year old boy with clusters of myoclonic and atonic seizures. Global development delay, with autistic features of unknown cause. Eight AEDs previously tried, ketogenic diet considered. Became seizure free on triple therapy. Case Three Eighteen year old girl with SCN1A-positive Dravet syndrome. Daily myoclonic, absence and tonic-clonic seizures, needing frequent hospital admissions. Mainly seizure-free since starting triple therapy, with better quality-of-life noted. Case Four Four year old girl with frequent episodes of status epilepticus. Global developmental delay, with mild cerebral atrophy on MR. Seizure-free since commencing triple therapy. Case Five Eleven year old boy with tonic-clonic and absence seizures, many prolonged. Global developmental delay with severe learning difficulties, and neuronal migration disorder found on MR. Triple therapy started, with occasional breakthrough seizures only when unwell. Conclusions: Stiripentol is a well-tolerated drug, licenced for use in Dravet Syndrome, when used as triple therapy with VPA and CLB. It is backed by robust evidence, with good long-term efficacy. Our experience in our challenging epilepsy cohort, with non-Dravet diagnoses, is surprising and gratifying.